Dagestan blunt-nosed viper, Macrovipera lebetina obtusa (Dwigubsky, 1832), venom. Venomics, antivenomics, and neutralization assays of the lethal and toxic venom activities by anti-Macrovipera lebetina turanica and anti-Vipera berus berus antivenoms. (June 2020) - Pla, Davinia; Quesada-Bernat, Sarai; Rodríguez, Yania; Sánchez, Andrés; Vargas, Mariángela; Villalta, Mauren; Mesén, Susana; Segura, Álvaro; Mustafin, Denis O.; Fomina, Yulia A.; Al-Shekhadat, Ruslan I.; Calvete, Juan J.
Abstract: We have applied a combination of venomics, in vivo neutralization assays, and in vitro third-generation antivenomics analysis to assess the preclinical efficacy of the monospecific anti- Macrovipera lebetina turanica (anti-Mlt) antivenom manufactured by Uzbiopharm® (Uzbekistan) and the monospecific anti- Vipera berus berus antivenom from Microgen® (Russia) against the venom of Dagestan blunt-nosed viper, Macrovipera lebetina obtusa (Mlo). Despite their low content of homologous (anti-Mlt, 5–10%) or para-specific (anti-Vbb, 4–9%) F(ab')2 antibody fragments against M. l. obtusa venom toxins, both antivenoms efficiently recognized most components of the complex venom proteome's arsenal, which is made up of toxins derived from 11 different gene families and neutralized, albeit at different doses, key toxic effects of M. l. obtusa venom, i.e., in vivo lethal and hemorrhagic effects in a murine model, and in vitro phospholipase A2, proteolytic and coagulant activities. The calculated lethality neutralization potencies for Uzbiopharm® anti-Mlt and anti-Vbb Microgen® antivenoms were 1.46 and 1.77 mg/mL, indicating that 1 mL of Uzbiopharm® and Microgen® antivenoms may protect mice from 41 to 50 LD50 s of Mlo venom, respectively. The remarkable degree of conservation of immunogenic determinants between species of the clades of European and Oriental viper, which evolved geographically segregated since the early Miocene, suggests an eventual window of opportunity for the treatment of envenomings by Eurasian snakes. Clearly, the rational use of heterologous antivenoms requires establishing their para-specificity landscapes. This paper illustrates the analytical power of combining in vitro and in vivo preclinical quantitative assays toward this goal. Graphical abstract: Image 1 Highlights: Efficacy against M. l. obtusa venom by two antivenoms was investigated. Quantification of lethality neutralizing antibodies was assessed. Anti- Vipera berus antivenom showed paraspecificity against M. l. obtusa venom. This study provides hints as how to improve the potency of the antivenoms sampled.